Increased Vulnerability to Pregnancy and Sexual Violence in Adolescents with Precocious Menstruation - Cezimbra, Giani Silvana Schwengber; Campos Junior, Dioclécio; Araujo Júnior, Edward; Guazzelli, Cristina Aparecida Falbo; Atallah, Álvaro Nagib (International Journal of Reproductive Medicine, 2020)
This cross-sectional, observational, and descriptive study was conducted to evaluate the association between age at menarche in the adolescent population and the age at sexual initiation, age at first pregnancy, and experience of sexual violence in the adolescent population visiting a primary health unit in Brazil. We recruited 201 female adolescents who visited the gynecology outpatient clinic of a Basic Health Unit in the Federal District of Brazil. These adolescents answered a questionnaire with regard to sexual and reproductive health during doctor’s appointments. To calculate the association, we recorded data for age at menarche, age at first sexual intercourse, age at first pregnancy, and experience of sexual violence. Pearson and Mann–Whitney correlation coefficient statistical tests were performed to evaluate the association between these variables. Mean age at menarche was lower among adolescents who became pregnant (p=0.0004) and those who experienced sexual violence (p=0.0008). Further, there was a strong association between age at menarche and age at first sexual intercourse (p<0.0001). This study also demonstrated that the earlier the age at menarche, the earlier was the age at sexual initiation and age at first unintended pregnancy and the greater was the risk of experiencing sexual violence. Early menarche may be considered a vulnerability factor during adolescence.